A narrative inquiry of international students' experiences in Indonesia: Language appraisal and transitivity analysis - Irayanti, Irma; Sapriya, Sapriya; Suryadi, Karim; Komalasari, Kokom; Hastowohadi, Hastowohadi (Journal of International Students, 2025)
This study explores the promotion of ethical behavior through intercultural education via a narrative inquiry research design. Seven international students from Madagascar, Libya, Turkmenistan, Thailand, and Malaysia participated, providing diverse perspectives on their experiences. The participants' narratives were analyzed through the lenses of transitivity and language appraisal, revealing nuanced insights into how intercultural education shapes ethical behavior. The findings highlight the transformative impact of intercultural learning environments on international students' intercultural development and decision-making processes. This research underpins the integration of intercultural education into curricula to foster ethical global citizens and offers practical implications for educators and policymakers seeking to cultivate inclusive, ethically aware educational settings.